Tunneling nanotubes: an alternate route for propagation of the bystander effect following oncolytic viral infection - Justin Ady; Venugopal Thayanithy; Kelly Mojica; Phillip Wong; Joshua Carson; Prassanna Rao; Yuman Fong; Emil Lou (Molecular Therapy: Oncolytics, 2016)
Tunneling nanotubes (TNTs) are ultrafine, filamentous actin-based cytoplasmic extensions which form spontaneously to connect cells at short and long-range distances. We have previously described long-range intercellular communication via TNTs connecting mesothelioma cells in vitro and demonstrated TNTs in intact tumors from patients with mesothelioma. Here, we investigate the ability of TNTs to mediate a viral thymidine kinase based bystander effect after oncolytic viral infection and administration of the nucleoside analog ganciclovir. Using confocal microscopy we assessed the ability of TNTs to propagate enhanced green fluorescent protein (eGFP), which is encoded by the herpes simplex virus NV1066, from infected to uninfected recipient cells. Using time-lapse imaging, we observed eGFP expressed in infected cells being transferred via TNTs to noninfected cells; additionally, increasing fluorescent activity in recipient cells indicated cell-to-cell transmission of the eGFP-expressing NV1066 virus had also occurred. TNTs mediated cell death as a form of direct cell-to-cell transfer following viral thymidine kinase mediated activation of ganciclovir, inducing a unique long-range form of the bystander effect through transmission of activated ganciclovir to nonvirus-infected cells. Thus, we provide proof-of-principle demonstration of a previously unknown and alternative mechanism for inducing apoptosis in noninfected recipient cells. The conceptual advance of this work is that TNTs can be harnessed for delivery of oncolytic viruses and of viral thymidine kinase activated drugs to amplify the bystander effect between cancer cells over long distances in stroma-rich tumor microenvironments.